2021
DOI: 10.1111/ene.14697
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and social support in a large population of people with multiple sclerosis recruited online through the COVID‐19 pandemic

Abstract: Background and purpose:The COVID-19 emergency may cause post-traumatic stress disorder (PTSD), and with regard to people with MS (pwMS) chronic exposure to a wide range of challenging life events has been shown to be correlated with worsening of neurological symptoms, increased lesion burden on brain magnetic resonance imaging and relapses. The aim was to investigate perceived stress, depression, perceived social support, habits and behaviour changes in pwMS through COVID-19 in comparison to a control group. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 25 publications
4
50
2
Order By: Relevance
“…Both depression and anxiety were elevated above the rates observed in the general population, but only marginally above typical levels for the MS population relative to prior studies. On the other hand, in a study conducted on pwMS during pandemic indicated increased perceived stress compared with healthy controls but in the same study, it has been observed that people with migraine were more stressful than pwMS ( Bonavita et al., 2020 ). In our study group, the perceived stress level was found to be high only in 11.0% and perceived stress was not associated with many factors such as gender, age, marital status, education level, employment status, disease duration, disability and income level.…”
Section: Discussionmentioning
confidence: 86%
“…Both depression and anxiety were elevated above the rates observed in the general population, but only marginally above typical levels for the MS population relative to prior studies. On the other hand, in a study conducted on pwMS during pandemic indicated increased perceived stress compared with healthy controls but in the same study, it has been observed that people with migraine were more stressful than pwMS ( Bonavita et al., 2020 ). In our study group, the perceived stress level was found to be high only in 11.0% and perceived stress was not associated with many factors such as gender, age, marital status, education level, employment status, disease duration, disability and income level.…”
Section: Discussionmentioning
confidence: 86%
“…Whether or not chronic stress predisposes MS patients to higher risks of developing relapses is controversial, partly due to the inter-study differences in terms of stress definition and measurement methods (Xie et al, 2020). However, we speculate that this evident psychological stress on RRMS patients (Stojanov et al, 2020, Bonavita et al, 2020 may have had an impact, at least partially, on the activity of their disease during this period, and it was more significant in patients who had not contracted COVID-19 during those times, probably facing chronically elevated levels of stress during the 9-10 months recorded in our study.…”
Section: Chronic Stress During the Covid-19 Pandemic And Considerations In Ms Patientsmentioning
confidence: 88%
“…Recently, Bonavita et al have surveyed a large number of MS patients to assess perceived stress, depression, and perceived social support. Unfortunately, a significantly higher proportions of MS patients, compared to healthy controls, were depressed (43.1% vs. 23.1%; p<0.001), experienced high levels of stress (58% vs. 39.8%; p<0.001), and less perceived social support (p<0.001) (Bonavita et al, 2020). These patients may experience high levels of chronic stress because of the pandemic, their clinical condition, and their immunosuppressive treatment regimens.…”
Section: Chronic Stress During the Covid-19 Pandemic And Considerations In Ms Patientsmentioning
confidence: 99%
“…The psychological impact of COVID-19 in terms of stress, negative emotional reactions (e.g., anxiety, depression), and traumatic responses has been extensively studied in the general population [39] and to a lower extent also in vulnerable populations, such as chronically ill patients, including patients with MS [15,[17][18][19][20][21][22][23]. Moreover, young adults are particularly vulnerable and at greater risk of developing adverse psychological symptoms during the pandemic, as demonstrated in a study by Forte and colleagues [40] that focused on people under the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges that would suggest a greater risk for developing negative emotional responses [16], studies exploring the psychological reaction of patients with MS found mixed results. Some studies highlighted high levels of anxiety [17,18] perceived stress [19] and depression [15,[18][19][20][21] while others did not find any worsening of emotional distress and also an improvement in some areas of quality of life [22,23]. Indeed, although further studies with larger samples are needed, it can be hypothesized that patients with MS managed to maintain an adequate level of wellbeing.…”
Section: Introductionmentioning
confidence: 99%